(untitled) (International Journal of Technology and Management Research, 2020)
Food emulsions are thermodynamically unstable mixtures which can be stabilized with the application of an emulsifier. In Ghana emulsifiers are imported, and this increases the final cost of food emulsions. In this study, gums obtained from three tree plant species in Ghana, i.e. Albizia zygia (Albizia), Khaya senegalensis (Khaya), and Anarcardium occidentale (Cashew), were used to stabilize oil-in-water emulsion, and the stability of the emulsions were measured after centrifugation at 1300 x g for 5 min, and upon pH adjustment (from 2 to 3.5). Quantity of gum (mass), solubility of gum in the continuous phase, viscosity, oil volume fraction, and pH were investigated to determine how they affect emulsion stability.The results indicated with the exception of viscosity, emulsion stability is influenced by all the other factors studied. In addition there was no significant difference (P<0.05) between the emulsion stabilities of food emulsions stabilized by gums of Cashew (0.77-0.86) and Acacia (0.78-0.87). The Pearson’s co-efficient of correlation indicated that the emulsion stability values of the emulsions positively correlated with the solubility of the gums (R2 =0.983 at P<0.05, and0.997 at P<0.01). Although there were no significant differences in the emulsion stability values of emulsions stabilized with Albizia and Khaya gums, both recorded significantly lower (P<0.05) emulsion stability values (0.76-0.85 and 0.75-0.81 respectively) than the Acacia gum (control). The Cashew gum has the potential to be utilized as an emulsifier in the food industry. Keywords: Emulsion, Emulsifier, Acacia gum, Oil-in-water Emulsion, Emulsion stability